Conjugated Bilirubin Differentially Regulates CD4+ T Effector Cells and T Regulatory Cell Function through Outside-In and Inside-Out Mechanisms: The Effects of HAV Cell Surface Receptor and Intracellular Signaling - Karla F. Corral-Jara; Jorge L. Trujillo-Ochoa; Mauricio Realpe; Arturo Panduro; Juan F. Gómez-Leyva; Yvonne Rosenstein; Alexis Jose-Abrego; Sonia Roman; Nora A. Fierro (Mediators of Inflammation)
We recently reported an immune-modulatory role of conjugated bilirubin (CB) in hepatitis A virus (HAV) infection. During this infection the immune response relies on CD4+ T lymphocytes (TLs) and it may be affected by the interaction of HAV with its cellular receptor (HAVCR1/TIM-1) on T cell surface. How CB might affect T cell function during HAV infection remains to be elucidated. Herein, in vitro stimulation of CD4+ TLs from healthy donors with CB resulted in a decrease in the degree of intracellular tyrosine phosphorylation and an increase in the activity of T regulatory cells (Tregs) expressing HAVCR1/TIM-1. A comparison between CD4+ TLs from healthy donors and HAV-infected patients revealed changes in the TCR signaling pathway relative to changes in CB levels. The proportion of CD4+CD25+ TLs increased in patients with low CB serum levels and an increase in the percentage of Tregs expressing HAVCR1/TIM-1 was found in HAV-infected patients relative to controls. A low frequency of 157insMTTTVP insertion in the viral receptor gene HAVCR1/TIM-1 was found in patients and controls. Our data revealed that, during HAV infection, CB differentially regulates CD4+ TLs and Tregs functions by modulating intracellular pathways and by inducing changes in the proportion of Tregs expressing HAVCR1/TIM-1.